Pendampingan Membuat Perlindungan Alami dari Nyamuk dengan Ekstrak Sereh Sprey dalam upaya mencegah Demam Berdarah di Desa Barugbug - Agustiawan, M Nassir; Saepudin, Eli Apud; Saputri, Cindi (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2024)
The assistance in making mosquito spray made from lemongrass extract aims to increase the awareness of the Barugbug Village community on the importance of preventing Dengue Fever (DHF) through natural means. Through the training of making mosquito spray, it is expected that the community can produce their own repellents that are effective and safe to use. This activity is also expected to reduce dependence on chemical products and improve the quality of life of the community. The results of the assistance showed an increase in community knowledge about DHF and how to prevent it, as well as an increase in community interest in producing natural products. This assistance actively involved the Barugbug Village community in DHF prevention efforts. Through training in making mosquito spray made from lemongrass extract, the community not only gained knowledge about medicinal plants, but also skills in producing natural products. This participatory approach is expected to increase community ownership of the DHF prevention program and encourage the formation of self-help groups that care about environmental health.